2021
DOI: 10.5194/wcd-2-1303-2021
|View full text |Cite
|
Sign up to set email alerts
|

The role of tropopause polar vortices in the intensification of summer Arctic cyclones

Abstract: Abstract. Human activity in the Arctic is increasing as new regions become accessible, with a consequent need for improved understanding of hazardous weather there. Arctic cyclones are the major weather systems affecting the Arctic environment during summer, including the sea ice distribution. Mesoscale to synoptic-scale tropopause polar vortices (TPVs) frequently occur in polar regions and are a proposed mechanism for Arctic cyclone genesis and intensification. However, while the importance of pre-existing tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 60 publications
4
24
0
Order By: Relevance
“…Recent studies have suggested that some Arctic cyclones may have been strongly influenced by TPVs (e.g. Simmonds and Rudeva, 2014;Tao et al, 2017;Gray et al, 2021). Understanding what causes this structural transition of summer Arctic cyclones and why they tend to have longer lifetimes than winter Arctic and extra-tropical cyclones is an area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that some Arctic cyclones may have been strongly influenced by TPVs (e.g. Simmonds and Rudeva, 2014;Tao et al, 2017;Gray et al, 2021). Understanding what causes this structural transition of summer Arctic cyclones and why they tend to have longer lifetimes than winter Arctic and extra-tropical cyclones is an area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the area of >70°N, the higher standard deviation extended from the coast of East Siberian Sea and Beaufort Sea, indicating that the high AOD airs over Northern Eurasia and Northern America were transported toward the North Pole as shown in the section 3.2. The synoptic activity over the Arctic was higher in summer (Clancy et al, 2021;Gray et al, 2021;Serreze and Barrett, 2008; manuscript submitted to Journal of Geophysical Research: Atmosphere 2004); hence, we investigate the contribution of Arctic cyclones on the Arctic AOD variability in summer in the following section.…”
Section: Comparison Of the Arctic Aod In Jraero Camsra And Merra2mentioning
confidence: 99%
“…The Arctic cyclones (ACs) in summer have a different threedimensional (3D) structure from mid-latitude cyclones (Tanaka et al, 2012) and wintertime ACs (Clancy et al, 2021). Gray et al (2021) presented the difference in the structures of the summertime ACs caused by their relationship to the tropopause polar vortex. Although Xian et al (2022) suggested that the AC frequency might not contribute to the Arctic AOD trend because the AC frequency had no significant trend (Vessey et al, 2020), the AC activity will influence the Arctic aerosol variability on the synoptic timescales; for example, ACs can contribute to the emission, transport, aging, and removal processes (e.g., wet deposition) of Arctic aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Arctic Cyclones (ACs) are considered as one of the most dangerous weather systems affecting the Arctic region (Bader et al, 2011), which are synoptic-scale low-pressure systems that form in or move into the Arctic region (Aizawa & Tanaka, 2016). Generally, ACs can be distinguished from extratropical cyclones by latitudes (Gray et al, 2021). Based on the Arctic System Reanalysis (ASR) data set, Tilinina et al (2014) found that 20% of ACs north of 55°N are below 980 hPa during 2000-2010, while the percentage increases to 24% in the Arctic Ocean region.…”
mentioning
confidence: 99%